Modo de vida dos imigrantes africanos na cidade de São Paulo: a trajetória dos angolanos - Costa, Beatriz Adão Pascoal da (2019)
The present study is aimed at understanding the phenomenon of African immigration in São Paulo, in particular, deals with the way of life of these Africans in the city of São Paulo: the trajectory of the Angolans, men and women who chose this city for a fresh start. Often they are victims of persecution, and without protection by home governments, immigrants are subjected to precarious living conditions involving rights violations. Partly because they feel they are intruders in another's country, and partly because of structural determinations, these immigrants are struggling in search of a better life's dream. Our focus here is to understand the way of life of Angolan immigrants and the path they have taken, the way of life and how they live in the daily life of the metropolis, and their access to the labor market. Bras is a central region of the city of São Paulo and it is the place where immigrants make their history. This research was carried out with the contribution of oral history methodology as a privileged source to understand the life trajectory of the Angolan immigrants in this city. We aim to interpret the phenomenon of immigration as a social factor, the focus of our observation. In this context, we seek to understand the reality of the subjects who submit to immigration as a condition for the possibility of better living conditions, based on the meanings attributed to them, despite the value vocabulary it brings from its origin. By focusing on the oral narrative, it seeks to reconcile the meanings brought by immigrants with those attributed to them, considering the set of laws and norms that legitimize immigration